Polyol Synthesis of Ultrathin Pd Nanowires via Attachment‐Based Growth and Their Enhanced Activity towards Formic Acid Oxidation. (19th August 2013) - Wang, Yi; Choi, Sang‐Il; Zhao, Xin; Xie, Shuifen; Peng, Hsin‐Chieh; Chi, Miaofang; Huang, Cheng Zhi; Xia, Younan
<x xml:space="preserve">Abstract</x> Palladium wavy nanowires with an ultrathin diameter of 2 nm are synthesized using the polyol method without the involvement of any template. The success of this synthesis relies on the use of a suitable precursor that could be reduced instantaneously to generate a large number of small Pd nanoparticles. Due to a quick depletion of precursor, the small nanoparticles were unable to grow in size through atomic addition. In the case of low surface charges and high surface energies, these small nanoparticles were forced to coalesce into ultrathin nanowires with a wavy morphology via an attachment mechanism. Thanks to the unique structure and involvement of twin defects, the as‐obtained Pd ultrathin nanowires show a catalytic current density of 2.5 times higher than the conventional Pd/C catalyst towards formic acid oxidation. This work not only offers a powerful route to the synthesis of nanowires through attachment‐based growth but also opens the door to the rational design and fabrication of novel metal nanostructures with enhanced properties.